2016
DOI: 10.2337/db15-1128
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Adipose Rab10-Dependent Insulin Signaling Causes Hepatic Insulin Resistance

Abstract: Insulin controls glucose uptake into adipose and muscle cells by regulating the amount of GLUT4 in the plasma membrane. The effect of insulin is to promote the translocation of intracellular GLUT4 to the plasma membrane. The small Rab GTPase, Rab10, is required for insulin-stimulated GLUT4 translocation in cultured 3T3-L1 adipocytes. Here we demonstrate that both insulin-stimulated glucose uptake and GLUT4 translocation to the plasma membrane are reduced by about half in adipocytes from adipose-specific Rab10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 55 publications
2
52
0
Order By: Relevance
“…Abnormalities in the cellular machinery that regulates Glut4 trafficking may also play a role. This is supported by studies showing that disruption of Glut4 trafficking in adipocytes by deleting Rab10 (Ras-related protein 10) also reduces glucose transport without impairing insulin signaling or Glut4 content (Vazirani et al, 2016). Indeed, loss of ChREBP in adipocytes delays insulin-stimulated Glut4 exocytosis.…”
Section: Discussionmentioning
confidence: 83%
“…Abnormalities in the cellular machinery that regulates Glut4 trafficking may also play a role. This is supported by studies showing that disruption of Glut4 trafficking in adipocytes by deleting Rab10 (Ras-related protein 10) also reduces glucose transport without impairing insulin signaling or Glut4 content (Vazirani et al, 2016). Indeed, loss of ChREBP in adipocytes delays insulin-stimulated Glut4 exocytosis.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, adipose-specific GLUT4 -/- mice exhibited insulin resistance in skeletal muscle and liver without affecting adiposity [208]. Furthermore, mice with adipose-specific Rab10 deletion, a GTPase required for insulin-stimulated GLUT4 translocation, displayed hepatic insulin resistance despite normal insulin suppression of plasma FFAs [209]. …”
Section: Insulin Resistance In the Adipose Tissuementioning
confidence: 99%
“…However, previous studies have demonstrated both Rab10-dependent and independent insulin signaling to Glut4 (Sadacca et al, 2013, Vazirani et al, 2016). Thus, we next sought to determine whether E4-ORF1 effect on Glut4 trafficking is dependent on AS160-Rab10 signaling module.…”
Section: Resultsmentioning
confidence: 93%
“…Rab10 ablation reduces Glut4 translocation by about 50% establishing that the full effect of insulin on Glut4 is the sum of Rab10-dependent and Rab10-independent mechanisms (Sano et al, 2007, Vazirani et al, 2016). Rab10 affects Glut4 translocation at a step prior to Glut4 vesicle docking to the PM (Bai et al, 2007, Sano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%